The persistence of (subnational) fortune : geography, agglomeration, and institutions in the new world (2012)
Using subnational historical data, this paper establishes the within country persistence of economic activity in the New World over the last half millennium. We construct a data set incorporating measures of pre-colonial population density, new measures of present regional per capita income and population, and a comprehensive set of locational fundamentals. These fundamentals are shown to have explanatory power: native populations throughout the hemisphere were found in more livable and productive places. We then show that high pre-colonial density areas tend to be dense today: population agglomerations persist. The data and historical evidence suggest this is due partly to locational fundamentals, but also to classic agglomeration effects: colonialists established settlements near existing native populations for reasons of labor, trade, knowledge and defense. We then show that high density (historically prosperous) areas also tend to have higher incomes today, and largely due to agglomeration effects: fortune persists for the United States and most of Latin America. Further, we show that extractive institutions, in our case, slavery, reduce persistence even if they do not overwhelm other forces in its favor.